The Forecasting Power of Task-Based Language Teaching and Self-Efficacy on Students' Speaking Performance - Dedi Sumarsono; Muliani Muliani; Abdul Kadir Bagis (Journal of Languages and Language Teaching, 2020)
This paper is aimed at finding out whether or not: (1) the students who were taught with Task-Based Language Teaching (TBLT) have better speaking performance than those who do not; (2) the students having high self-efficacy have better speaking skill than those having low self-efficacy; and (3) there is an interaction between teaching methods and self-efficacy on students' speaking performance. The research was conducted at SMAN 8 Mataram. Each class was divided into two groups (the students having high (32 students) and low self-efficacy (30 students). The techniques used to collect the data were speaking test and self-efficacy questionnaire. The data was analyzed by using multifactor analysis of variance 2x2 through SPSS 21 software. The finding shows that Task-Based Language Teaching (TBLT) improved the students' speaking performance as this method focused on giving the students task to be discussed during the teaching and learning process. Their self-efficacy also influenced students' speaking performance. The higher the students' self-efficacy, the better speaking skill could be performed. However, the study's finding didn't suggest that TBLT is more effective in enhancing students' speaking performance for the students having high or low self-efficacy as there is no interaction between the teaching method and self-efficacy on the students' speaking performance.